IMPLEMENTASI PERATURAN BUPATI TANAH LAUT NOMOR 12 TAHUN 2019 TENTANG PENGELOLAAN KEUANGAN DESA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN TANAH LAUT - Irawanto; Dody Saputra; M. Jamili; Ali Khamdan; Mukhlan Khariry; Akhmad Abdurahman (stiatabalong.ac.id, 2025)
Tanah Laut Regency Government has issued a policy on village financial management, necessitating research into its implementation. This study aims to describe and analyze the implementation of Tanah Laut Regent Regulation Number 12 of 2019 concerning Village Financial Management, and to identify the obstacles encountered during its implementation. This research employs a qualitative method designed to provide an in-depth understanding of the implementation of the regional regulation on village financial management. Data were collected through interviews, observations, and documentation. Interviews were conducted with key informants, including the head of the relevant agency (Dinas), financial staff from the Community Empowerment Agency (Dinas Pemberdayaan Masyarakat), and five village heads. The results indicate that village financial management is not yet fully transparent, accountable, participatory, orderly, and adhering to budget discipline. The success of policy implementation is influenced by two key factors: policy content variables and policy environment variables. Overall, the policy has been implemented reasonably well; however, several indicators remain suboptimal, particularly regarding the desired degree of change in areas such as participation, transparency, and accountability. It is hoped that the implementation of this policy will not lead to corrupt practices by village officials. Keywords: Village, Financial, Management